A positive role for nucleosome mobility in the transcriptional activity of chromatin templates: restriction by linker histones. - Ura, K (1995)
Nucleosome mobility facilitates the transcription of chromatin templates containing only histone octamers. Inclusion of linker histones in chromatin inhibits nucleosome mobility, directs nucleosome positioning and represses transcription. Transcriptional repression by linker histone occurs preferentially on templates associated with histone octamers relative to naked DNA. Mobile nucleosomes and the restriction of mobility by linker histones might be expected to exert a major influence on the accessibility of chromatin to regulatory molecules.